Does index insurance help households recover from disaster? Evidence from IBLI Mongolia - Veronika Bertram-Huemmer; Kati Kraehnert (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This paper investigates the impact of indemnity payments from index insurance on the asset recovery of households after a catastrophic weather disaster occurs. Our focus is on the Index-Based Livestock Insurance (IBLI) in Mongolia. We analyze the effect of IBLI indemnity payments after a once-in-50-year winter disaster struck Mongolia over 2009/10. The database for our analysis is three waves of a household panel survey implemented in western Mongolia. We employ the bias-corrected matching estimator to account for selection into purchasing IBLI. Results indicate that pastoralist households purchasing IBLI before the shock recover faster from shock-induced asset losses than comparable non-insured households. We find a significant, positive and economically large effect of IBLI indemnity payments on herd size one and two years after the shock. In the medium term - three and four years after the shock - the effect slowly vanishes. Results are robust to defining post-shock livestock recovery in different ways, varying the number of matches per observation, the choice of covariates, and the use of alternative propensity score estimators. An analysis of shock coping strategies as well as complementary qualitative interviews conducted in the field suggest that indemnity payments help herders to avoid selling and slaughtering animals and smooth their productive asset base. Also, IBLI appears to have relieved households from credit constraints. Our study is among the first to provide evidence on the beneficial effects of index insurance after a weather shock in a developing economy.
Keywords: O12; O13; Q14; 330; index insurance; livestock; weather shocks; Mongolia